Construction and decoding of BCH codes over finite commutative rings - De Andrade, Antonio Aparecido [UNESP]; Palazzo Jr., Reginaldo (Elsevier, 1999)
BCH codes over arbitrary finite commutative rings with identity are derived in terms of their locator vector. The derivation is based on the factorization of xs -1 over the unit ring of an appropriate extension of the finite ring. We present an efficient decoding procedure, based on the modified Berlekamp-Massey algorithm, for these codes. The code construction and the decoding procedures are very similar to the BCH codes over finite integer rings. © 1999 Elsevier B.V. All rights reserved.
Keywords: BCH codes; Error-location numbers; Forney's method; Galois extension; Modified Berlekamp-Massey algorithm; Syndrome calculation